2013
DOI: 10.1111/tbed.12107
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium aviumsubsp.paratuberculosisSheep Strains Isolated from Cyprus Sheep and Goats

Abstract: Paratuberculosis, caused by Mycobacterium avium subsp. paratuberculosis (Map), is a chronic incurable infection of intestinal tract of animals. Molecular characterization of Map isolates classifies them into two major groups, 'Cattle' or Type II and 'Sheep' or Type I/III with a different phenotype, epidemiology, virulence and pathogenesis. The aim of this study was to examine 192 Map ELISA-positive sheep and goats from Cyprus using faecal culture and genotype Map isolates using IS1311 PCR and restriction endon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Most of these studies were based on existing isolate collections, and showed a fair amount of homogeneity within M. paratuberculosis strains and revealed that M. paratuberculosis strains from human infections were less diverse compared to cattle (Wynne et al, 2011). Results were derived from several methods making it difficult to make direct comparisons, including IS1311 restriction fragment length polymorphism (RFLP) analyses (Whittington et al, 2000;Motiwala et al, 2003;Singh et al, 2010b;Okuni et al, 2012;Liapi et al, 2015), (Stevenson et al, 2009;Fernandez-Silva et al, 2012) randomly amplified polymorphic DNA (RAPD) (Pillai et al, 2001), multi-locus short sequence repeat sequencing (MLSSR) (Fernandez-Silva et al, 2012), Multiplex PCR of IS900 integration loci (MPIL) (Motiwala et al, 2004), short sequence repeats (SSR) (Ghadiali et al, 2004), and single nucleotide polymorphisms (SNPs) (Wynne et al, 2011). A tally of the type of M. paratuberculosis (e.g.…”
Section: Molecular Epidemiology Of M Paratuberculosismentioning
confidence: 99%
“…Most of these studies were based on existing isolate collections, and showed a fair amount of homogeneity within M. paratuberculosis strains and revealed that M. paratuberculosis strains from human infections were less diverse compared to cattle (Wynne et al, 2011). Results were derived from several methods making it difficult to make direct comparisons, including IS1311 restriction fragment length polymorphism (RFLP) analyses (Whittington et al, 2000;Motiwala et al, 2003;Singh et al, 2010b;Okuni et al, 2012;Liapi et al, 2015), (Stevenson et al, 2009;Fernandez-Silva et al, 2012) randomly amplified polymorphic DNA (RAPD) (Pillai et al, 2001), multi-locus short sequence repeat sequencing (MLSSR) (Fernandez-Silva et al, 2012), Multiplex PCR of IS900 integration loci (MPIL) (Motiwala et al, 2004), short sequence repeats (SSR) (Ghadiali et al, 2004), and single nucleotide polymorphisms (SNPs) (Wynne et al, 2011). A tally of the type of M. paratuberculosis (e.g.…”
Section: Molecular Epidemiology Of M Paratuberculosismentioning
confidence: 99%
“…Thus, some reports indicated higher sensitivity and specificity values from serum or milk samples than from faeces (Liapi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sheep in Spain have been found to be mainly infected with type S strains, whereas goats are infected with both type S and type C strains. Furthermore, the type S strain has been considered as the primary genetic type that infects sheep and goats in Cyprus [ 35 ]. It is generally believed that ovine paratuberculosis is mostly caused by type S strains of MAP in sheep.…”
Section: Discussionmentioning
confidence: 99%